Surgical Management of Benign Prostatic Hyperplasia in A Tertiary Health Centre - Najeem Idowu; Safiriyu Raji; Abraham Amoo; Suliat Adeleye-Idowu (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Benign prostatic hyperplasia (BPH) is a common cause of lower urinary tract symptoms with attendant negative impact on the quality of life. The management of benign prostatic hyperplasia (BPH) could be medical or surgical. The indications for surgical intervention include severe lower urinary tract symptoms and failed medical therapy among others. Common surgical options for BPH are Transurethral resection of the prostate (TURP), Holmium laser resection of the prostate (HoLEP) and open simple prostatectomy among others. The traditional gold standard surgical intervention for BPH remains TURP. Due to lack of facilities and expertise open simple prostatectomy is the most common surgical intervention for BPH in a developing economy like ours. This study was aimed at presenting pattern of presentation of patients with symptomatic benign prostatic hyperplasia and open simple prostatectomy in the management of BPH and its outcome in our environment. Methods. We retrospectively reviewed patients that were managed surgically for benign prostatic hyperplasia between July 2013 and June 2022 in a tertiary health center located in sub-Saharan African. Information extracted and analyzed from the hospital records included; patient’s biodata, symptoms on presentation, findings on digital rectal examination (DRE), laboratory investigations including PSA, indications for surgery, surgical procedures, type of anesthesia and post-operative complications. Results. A total of 151 cases of open simple prostatectomy were studied. Rate of prostatectomy over the studied period was 4.2%. The age range of the patients was 42-90 years with a mean of 67.6 +/ 8.7 years. All the patients presented with lower urinary tract symptoms. The pre-operative serum prostate specific antigen range was 1-46ng/ml with a mean of 7.38+/ 8.95. The most common indication for surgery was failed medical therapy. Ninety patients (59.67%) had retropubic simple prostatectomy. The surgeries were done predominantly under regional anesthesia. The duration of surgery ranged between 53-150 minutes with a mean of 132.08minutes fifty-one patients (37.33%) received blood transfusion. Thirty-three patients (21.85%) developed post-operative complications. The most common complication was surgical site infection. There was no mortality. Voiding was satisfactory in all our patients. Conclusion. Open simple prostatectomy remains an effective option for symptomatic BPH especially in a poor resource setting. This could serve as policy frame work for capacity building in the field of urology. Cite this article: Idowu N, Raji S, Amoo A, Adeleye-Idowu S. Surgical Management of Benign Prostatic Hyperplasia in A Tertiary Health Centre. Alq J Med App Sci. 2022;5(2):606-611. https://doi.org/10.5281/zenodo.7474474